Horizontal gene transfer of acetyltransferases, invertases and chorismate mutases from different bacteria to diverse recipients - Noon, Jason B.; Baum, Thomas J. (BMC evolutionary biology, 2016)
Hoplolaimina plant-parasitic nematodes (PPN) are a lineage of animals with many documented cases of horizontal gene transfer (HGT). In a recent study, we reported on three likely HGT candidate genes in the soybean cyst nematode Heterodera glycines, all of which encode secreted candidate effectors with putative functions in the host plant. Hg-GLAND1 is a putative GCN5-related N-acetyltransferase (GNAT), Hg-GLAND13 is a putative invertase (INV), and Hg-GLAND16 is a putative chorismate mutase (CM), and blastp searches of the non-redundant database resulted in highest similarity to bacterial sequences. Here, we searched nematode and non-nematode sequence databases to identify all the nematodes possible that contain these three genes, and to formulate hypotheses about when they most likely appeared in the phylum Nematoda. We then performed phylogenetic analyses combined with model selection tests of alternative models of sequence evolution to determine whether these genes were horizontally acquired from bacteria. Mining of nematode sequence databases determined that GNATs appeared in Hoplolaimina PPN late in evolution, while both INVs and CMs appeared before the radiation of the Hoplolaimina suborder. Also, Hoplolaimina GNATs, INVs and CMs formed well-supported clusters with different rhizosphere bacteria in the phylogenetic trees, and the model selection tests greatly supported models of HGT over descent via common ancestry. Surprisingly, the phylogenetic trees also revealed additional, well-supported clusters of bacterial GNATs, INVs and CMs with diverse eukaryotes and archaea. There were at least eleven and eight well-supported clusters of GNATs and INVs, respectively, from different bacteria with diverse eukaryotes and archaea. Though less frequent, CMs from different bacteria formed supported clusters with multiple different eukaryotes. Moreover, almost all individual clusters containing bacteria and eukaryotes or archaea contained species that inhabit very similar niches. GNATs were horizontally acquired late in Hoplolaimina PPN evolution from bacteria most similar to the saprophytic and plant-pathogenic actinomycetes. INVs and CMs were horizontally acquired from bacteria most similar to rhizobacteria and Burkholderia soil bacteria, respectively, before the radiation of Hoplolaimina. Also, these three gene groups appear to have been frequent subjects of HGT from different bacteria to numerous, diverse lineages of eukaryotes and archaea, which suggests that these genes may confer important evolutionary advantages to many taxa. In the case of Hoplolaimina PPN, this advantage likely was an improved ability to parasitize plants.